Kinesin family member 3A stimulates cell proliferation, migration, and invasion of bladder cancer cells in vitro and in vivo. Issue 5 (2nd May 2021) - Zhou, Qingchun; Yu, Juan; Zheng, Qingyou; Wu, Tao; Ji, Ziliang; Zhuo, Yumin
Abstract : Bladder cancer is one of the most common malignant tumors of the urinary system, with high morbidity and mortality. At present, the survival rates and prognosis of patients with bladder cancer are still relatively low; thus, there remains a need to improve prognosis by identifying novel targets. Kinesins (kinesin superfamily proteins) are a series of microtubule‐based motor proteins that mediate various types of cellular processes. Kinesin family member 3A (KIF3A) is critical for cytoplasm separation in mitosis, and it has been reported to be misexpressed in multiple types of cancer. However, its effects on the progression and development of bladder cancer remain unclear. Herein, we report that KIF3A is highly expressed in human bladder cancer. We identified a significant correlation between KIF3A and clinical features, including clinical stage ( P  = 0.047), pathological tumor status ( P  = 0.045), lymph node status ( P  = 0.041) and metastasis ( P  = 0.035). KIF3A expression was also correlated with poor prognosis of patients with bladder cancer. Our results further indicated that KIF3A ablation resulted in cell cycle arrest; blocked the proliferation, migration and invasion of bladder cancer cells in vitro ; and restrained tumor growth in mice in a microtubule‐dependent manner. In summary, our findings suggest that KIF3A is a potential therapeutic target for bladder cancer. Abstract : We found that kinesin family member 3A (KIF3A) was highly expressed in human bladder cancer tissues. Our results further indicated that KIF3A ablation resulted in cell cycle arrest and blocked the proliferation, migration and invasion of bladder cancer cells in a microtubule‐dependent manner. Importantly, our findings indicate that KIF3A could serve as a promising therapeutic target for bladder cancer treatment.